Report on the Treatment of MSME Insolvency - World Bank Group (World Bank, Washington, DC, 2017)
Micro, small, and medium enterprises (MSMEs) are among the largest commercial users of insolvency systems. MSMEs are a significant part of the global economy – and just as there are large numbers of MSMEs, there are large numbers of MSME insolvencies. However, there are a very few specialized legal regimes for MSME insolvency; most jurisdictions treat MSME insolvencies the same as for other corporate entities, or conversely, natural persons, despite MSMEs' unique attributes. This report considers the specific challenges of insolvent MSMEs (including the difficulties of defining MSMEs and distinguishing them from large corporate entities); reviews and analyzes how legislation in different jurisdictions deals with the challenges of MSME insolvency; and considers if existing international standards are sufficient to address MSME insolvency.